2020
DOI: 10.32678/loquen.v13i2.3588
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Lecturer's feedback quality and the Students' engagement in Online Learning

Abstract: This study aimed to reveal the lecturer’s feedback quality intertwined with students’ engagement in online learning through a WhatsApp group. Also, it unraveled the follow-up actions conducted by the students regarding the feedback. 24 graduate students studying in one of the universities in Bandung city involved. A mixed-method, an explanatory sequential design, was used. Utilizing questionnaires, the study reveals that with a mean of 82.38 and standard deviation of 6.51, the lecturer’s feedback was deemed go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Thereby, several considerations need to be noticed in giving effective feedback during learning, such as 1) a focus on students' performance rather than their qualities; 2) a focus on students' performance rather than their characteristics, and 3) a focus on students' performance rather than their characteristics. 3) compatibility with the assignment's goal; 4) timing, e.g., needed at the right moment; 5) utility, i.e., providing instructions on what to do (Sugianto & Prasetyo, 2020).…”
Section: Challenges Faced By Teachers In Giving Feedbackmentioning
confidence: 99%
“…Thereby, several considerations need to be noticed in giving effective feedback during learning, such as 1) a focus on students' performance rather than their qualities; 2) a focus on students' performance rather than their characteristics, and 3) a focus on students' performance rather than their characteristics. 3) compatibility with the assignment's goal; 4) timing, e.g., needed at the right moment; 5) utility, i.e., providing instructions on what to do (Sugianto & Prasetyo, 2020).…”
Section: Challenges Faced By Teachers In Giving Feedbackmentioning
confidence: 99%
“…Furthermore, it was similar to the research done by Sugianto & Prasetyo. It showed that students' engagement in online learning during the pandemic was good (Sugianto & Prasetyo, 2020).…”
Section: Introductionmentioning
confidence: 99%